(untitled) (International Journal of Engineering and Computer Science, 2013)
In this paper infrastructure as a service (IaaS), development and runtime platforms as a service (PaaS), and software and business applications as a service (SaaS). Clients not having any resources and data are guaranteed to be available and ubiquitously easy to get to by means of Web services and Web APIs “in the Cloud”. In the condition of cloud computing, this implies a significant, principle business decision whether to own and preserve a data center or outsource operations to the cloud. In Challenges and the opportunities are bond with the availability or performance of software running in the cloud, as well as privacy and data control. IT resources that is actually needed; for the service provider, better resource utilization of existing infrastructure is achieved through a multi-tenant architecture. In This paper suggest in trade-offs among service quality attributes, such as availability, distributed data consistency, service runtime presentation, and privacy in cloud computing.